Investigating the role of self-sacrificing prosociality in intragroup and intergroup contexts - Katna, Dashalini P. (Nanyang Technological University, 2020)
Parochial cooperation theories assume that strongly self-sacrificing members primarily desire and seek to achieve ingroup-favouring outcomes, and consequently become prepared to bear extreme costs to themselves. This altruism to help, however, does not always extend into intergroup contexts. Instead, the motivation to harm outgroups may surpass the motivation to enhance the ingroup’s welfare. Such occurrences challenge the principal premise of parochial cooperation accounts, underscoring not all highly selfsacrificing members may prioritize outcomes of ingroup well-being over outgroup harm. The central hypothesis of this thesis predicted that individuals who are highly self-sacrificing towards the ingroup in intragroup settings would strongly anticipate hostility from the outgroup, and in consequence, would harm the outgroup relative to exclusively ensuring instrumental ingroup benefit, ingroup gain at the outgroup’s expense, or personal gain in intergroup settings. This relationship was conceptualized as the Costly Self-sacrificial Aggression (CSA) framework and tested using six studies. Studies 1 to 3 employed decision-making tasks in minimal group paradigms. Participants played an intragroup task that measured their self-sacrificing prosociality, followed by an intergroup task which measured personally-costly pursuit of outgroup aggression. Studies 1 (N = 120) and 2 (N = 210) showed that self-sacrificing prosociality was positively predictive of outgroup harm. Study 3 (N = 106) found that self-sacrificing prosociality was associated with increased outgroup aggression, among members with high anticipations of outgroup hostility, only in the absence of outgroup threat. Studies 4 to 6 integrated the findings into a serial mediational pathway from identity fusion to outgroup aggression, through self-sacrificial readiness and anticipations of outgroup hostility. The studies utilized real group identities, issues, and perceptions within the U.S. context. Studies 4 (N = 299) and 5 (N = 376) revealed indirect effects of U.S. identity salience on restrictive policies toward outgroups like radical Islamic groups and malicious foreign organisations, that emerged through increased self-sacrificial readiness and anticipated outgroup hostility. Study 6 (N = 164) found that social identity complexity negatively predicted support for punitive policies toward an outgroup, through greater perceived distinctiveness of ingroup memberships, unwillingness to self-sacrifice, and anticipations of outgroup positivity. The studies largely examined U.S. samples which may limit external validity. Building on one another, the studies demonstrate consistent support that serves as preliminary confirmatory evidence for the CSA framework, implying that highly self-sacrificing members may initiate and posture outgroup aggression as a strategic priority in intergroup conflicts.